Identification of strong candidate genes for backfat and intramuscular fatty acid composition in three crosses based on the Iberian pig - Crespo-Piazuelo, Daniel; Criado-Mesas, Lourdes; Revilla, Manuel; Castelló, Anna; Noguera, José L.; Fernández, Ana I.; Ballester, Maria; Folch, Josep M. (Scientific reports, 2020)
Meat quality has an important genetic component and can be modified by the fatty acid (FA) composition and the amount of fat contained in adipose tissue and muscle. The present study aimed to find genomic regions associated with the FA composition in backfat and muscle ( longissimus dorsi ) in 439 pigs with three different genetic backgrounds but having the Iberian breed in common. Genome-wide association studies (GWAS) were performed between 38,424 single-nucleotide polymorphisms (SNPs) covering the pig genome and 60 phenotypic traits related to backfat and muscle FA composition. Nine significant associated regions were found in backfat on the Sus scrofa chromosomes (SSC): SSC1, SSC2, SSC4, SSC6, SSC8, SSC10, SSC12, and SSC16. For the intramuscular fat, six significant associated regions were identified on SSC4, SSC13, SSC14, and SSC17. A total of 52 candidate genes were proposed to explain the variation in backfat and muscle FA composition traits. GWAS were also reanalysed including SNPs on five candidate genes ( ELOVL6 , ELOVL7 , FADS2 , FASN , and SCD ). Regions and molecular markers described in our study may be useful for meat quality selection of commercial pig breeds, although several polymorphisms were breed-specific, and further analysis would be needed to evaluate possible causal mutations.